The crystal structure of veenite. (1st April 2017) - Topa, Dan; Makovicky, Emil
The crystal structure of veenite is reported for the first time from a sample from the type locality of Madoc (Ontario, Canada). It has been solved and refined by X-ray single-crystal diffraction on the basis of 4973 observed reflections (with Fo > 4σ(Fo)) with a final R1 = 0.0396. Veenite is monoclinic P21, with unit-cell parameters a = 8.429(2), b = 26.069(5), c = 8.962(2) Å, β = 117.447(2)o. The bulk veenite composition is Ag0.15Pb16.029Sb8.836As6.99S39.95 (for Z = 1) corresponding to N = 4.09 (Me8NS8N + 8, theoretical value is 4.0), with the percentage of the Ag-(As, Sb) substituted end-member only equal to 3.51 mol.%, i.e., a nearly pure Pb-Sb-As sulfosalt. The crystal structure is typical for the N = 4 sartorite homologue, with zig-zag walls of trigonal coordination prisms of Pb which separate slabs of diagonally oriented double-layers populated by Sb and As with partial Pb substitution. Orientation of three-membered crankshaft chains formed by strong (As, Sb) – S bonds on the two surfaces of double-layers differs substantially from that in dufrénoysite, which is a pure Pb-As (N = 4) sulfosalt.